THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN TEH POCHI INDONESIA - Akbar Jaya (Journal of Islamic Banking, 2024)
This study investigates the impact of service quality on customer satisfaction at Teh Pochi. The research sample consists of 83 customers of Teh Pochi who have made repeat purchases, selected through an accidental sampling method. Data were gathered using a questionnaire designed with a Likert scale to measure responses. The analysis was conducted using a simple regression analysis method via the SPSS 16 application. The findings from the t-test reveal that service quality significantly influences customer satisfaction, with a significance value of 0.000, which is less than the threshold of 0.05. This indicates a strong statistical relationship between the two variables. Furthermore, the coefficient of determination test results in an R Square value of 0.485, suggesting that 48.5% of the variation in customer satisfaction can be attributed to service quality. The remaining 51.5% is influenced by other factors not examined in this study. These results underscore the importance of maintaining high service quality to enhance customer satisfaction, while also indicating that other variables should be explored to fully understand the drivers of customer satisfaction at Teh Pochi.